Political Aspirations and Perils of Security - Edström, H. author. aut Link
XIII, 265 p.
Keywords: This book comprises of a range of case studies of military strategy, based on UN documents, observing and concluding the effectiveness of each individual case. Edstrom and Gyllensporre analyse the UN's military strategy, its consequences and its potential to fulfil political ambitions.